Prevention, screening and therapy of thyroid diseases and their cost-effectiveness - Dietlein, M.; Moka, D.; Schmidt, M.; Theissen, P.; Schicha, H. (Nuklearmedizin - NuclearMedicine, 2003)
Cost-effectiveness analyses focused on benign thyroid diseases are under-represented in the literature. The calculation of costs per additionally gained life year is difficult: The benefit of prevention is shifted into the distant future. The influence of an untreated subclinical thyroid disease on life expectancy can only be demonstrated by a long-term follow-up and by epidemiological databases. Iodine supplementation and programs for the prevention of tobacco smoking (primary prevention) are very cost-effective. Smoking increases the risk both of multinodular goiter and of Graves’ disease. Screening programs (secondary prevention) are discussed for the laboratory parameters thyrotropin (TSH), calcium and calcitonin. TSH testing seems to be very cost-effective for epidemiological considerations in a certain lifespan (newborn, pregnancy, postpartal, older persons, hospitalisation due to acute diseases) and in persons with previously elevated TPO-antibodies or TSH-values >2 mU/l, but dedicated cost-effectiveness analyses are lacking. On the other hand, the cost-effectiveness of a routine TSH testing beyond the age of 35 years has been shown by a high-quality decision analysis. Therapeutic strategies (tertiary prevention) aim at the avoidance of complications (atrial fibrillation, myocardial infarction, death for cardiac reasons) and of iatrogenic complications. Examples of a tertiary prevention are: firstly the definitive therapy of Graves’ disease in patients who have an increased risk of relapse after antithyroid drugs (ATD), secondly the radioiodine therapy for subclinical hyperthyroidism and the radioiodine therapy of large goiters in older patients or in patients suffering from a relevant comorbidity. Cost-effectiveness analyses for different therapeutic strategies of Graves’ disease were published using a lifelong time-horizon. The ablative radioiodine dose-regime is cost-effective as a first line therapy if the risk of relapse after ATD exceeds 60%.
Keywords: Thyroid diseases; prevention; screening; cost-benefit; cost-effectiveness